Income Optimization of Dairy Farm to Increase National Milk Production - Kusnadi, Uka; Juarini, E (Indonesian Animal Sciences Society, 2007)
The program to improve national milk production over the past years has not been well targeted. This is indicated by the slow increase of dairy population and milk production that could not meet the increasing demand. It should be apparently focus on income generation of dairy farmers to increase their welfare so that they are willing to improve their dairy business that will affect national milk production. Implementation of economical dairy management and technology, could increase milk production, hence improve the farmerâs income. This could be done through several ways, i.e.: economical dairy composition, optimization of dry period and improvement milk hygiene. All these aspects including technical aspect are discussed in this paper. Apart from above, income optimalization could also be done by reducing the price of feed concentrate, raising only productive dairy cows and managing milk cooperative efficiently. Key words: Dairy, business, optimalization, income